Measurement of the derivative 'ZW' for an oscillating aerofoil - Buchan, A. L.; Harris, K. D. (College of Aeronautics, 1950)
This report presents the results of experimental measurements of the damping derivative coefficient zw for constant chord rigid wings of various aspect ratios having sweepback angles of zero and 450. The results for the rectangular wings Flow substantial agreement with the unsteady aerofoil theory developed by TI.P. Jones $2) The dependence of Zvi upon frequency parameter is as given by theory and is much less than for two dimensional flow, but the numerical results are approximately 10 per cent below the theoretical. This is attributed to the large trailing edge angle 22° of the N.A.C.A. 0020 section used for the model aerofoils. The effect of sweepback is to decrease the numerical value of z , but this effect is much less pronounced, for low than for high aspect ratios. For aspect ratios 5 and 3 the numerical value is greater than would be given by a factor of proportionality equal to the cosine of the angle of sweepback. The measurements were corrected for tunnel interference by a method based on the theoretical work of 7.P.Jones.(1)